Kedudukan Hukum Pidana Terkait Adanya Peredaran Narkotika di Indonesia Ditinjau dari Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika - Rahmad Teguh (Fakultas Hukum Universitas Islam Jember, 2020)
This study is understood as a library research (library research), such as a study onsecondary data. In conclusion, the law enforcement against Narcotic Crimes according to Law on Narcotics shall give sanction of imprisonment, criminal fines, life imprisonment and other sanctions. The protection of child abuse of narcotics from victimology aspects is rehabilitated due to the child as a perpetrator and victim. The International Law on drug trafficking is the policy on preventing narcotic crimes originally provided in the United Nation's Single Convention on narcotic drugs in 1961.